Oral health-related quality of life in the East African community: a scoping review - Aminu, Kafayat; Jayasinghe, Rasika Manori; Uwambaye, Peace; Salami, Afeez; Murererehe, Julienne; Ineza, Marie Claire; Ntigura, Eustache; Ober-Oluoch, Jenipher; Milanes, Danilo Zambrano; Jayasinghe, Ruwan Duminda; Amzat, Jimoh; Kanmodi, Kehinde Kazeem (BMC oral health, 2025)
Limited access to oral healthcare and substantial untreated cases raises concerns about the rising burden of oral conditions in East Africa. This scoping review aimed to map the existing evidence on oral health status in relation to oral health-related quality of life (OHRQoL) across the East African Community (EAC). This scoping review was conducted based on the recommendations of Arksey and O'Malley's guidelines and reported based on the PRISMA-ScR checklist. Ten electronic databases were searched, using relevant keywords informed by the PCC (Population-Concept-Context) framework. The retrieved articles were deduplicated and screened for eligibility. Twenty-eight eligible articles were finally included in this review. The data charted from the included articles were collated, summarized, and reported thematically. Oral health conditions were highly prevalent in East Africa, ranging from 15.8 to 83.0%, with dental caries being the most common. Prevalence and impact varied across socio-demographic factors, including age, gender, education, and place of residence. Clinical factors such as DMFT/dmft scores and pain levels, and knowledge of preventive practices, also played a crucial role in influencing oral health outcomes. While many reported satisfactions with their oral health, oral conditions significantly impacted their quality of life, disrupting essential activities like eating, sleeping, hygiene, relaxation, and social interaction. Despite the widespread occurrence and associated discomfort, the majority failed to seek dental care, resulting in persistent daily challenges and diminished overall well-being. A high prevalence of oral conditions with serious impacts on quality of life and wellbeing was observed in the EAC. Given the satisfaction with oral health and the poor attitude towards seeking help for oral issues despite experiencing pain, we recommend future research to explore, identify, and implement contextually and culturally relevant interventions that will be tailored to the specific oral health needs of East African populations.